Clinical case studies in long-term care psychiatry navigating common mental health challenges in geriatric care - Gibfried, Matthew; Grossberg, George T. (Cambridge University Press, 2025)
The mental healthcare of older adults can lead to age specific challenges, however, many healthcare settings have limited access to expert geriatric psychiatric consultation. This compelling book provides a comprehensive compilation of real-life cases involving the psychiatric care of older adults in the long-term care setting. Providing practical guidance for healthcare professionals who work regularly with older adults, the chapters cover key topics such as neurocognitive disorders, mood disorders, anxiety disorders, psychotic disorders, end-of-life mental health care, and sexuality issues in older adults. Offering all the information necessary for the diagnosis and formulation of treatment plans for a wide variety of psychiatric presentations, the book covers pharmacologic and non-pharmacologic options for each disorder to assist healthcare professionals in providing well-rounded care. For all those involved in the prevention, assessment, diagnosis, and management of neuropsychiatric disorders in long-term care populations
Title from publisher's bibliographic system (viewed on 18 Oct 2024)
Keywords: Geriatric psychiatry; Older people / Mental health